Microbiological Agar Diffusion Assay for Metronidazole Concentrations in Serum - Levison, Matthew E. (1974)
An agar diffusion method using paper disks on plates seeded with Clostridium perfringens and incubated anaerobically to assay serum levels of metronidazole is described. The lowest serum metronidazole concentration that could be measured was 0.7 μg/ml, and the average error was 4% for 5 μg/ml. This assay could measure metronidazole in the presence of gentamicin or in the presence of penicillin, with the use of penicillinase incorporated into the assay plates, or in presence of penicillin, methicillin, and cephalothin with prior exposure of the specimen to beta-lactamase.